2021
DOI: 10.21203/rs.3.rs-253174/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DHHC21 Deficiency Attenuates Renal Dysfunction During Septic Injury

Abstract: Renal dysfunction is one of the most common complications of septic injury. One critical contributor to septic injury-induced renal dysfunction is renal vascular dysfunction. Protein palmitoylation serves as a novel regulator of vascular function. Here, we examined whether palmitoyl acyltransferase (PAT)-DHHC21 contributes to septic injury-induced renal dysfunction through regulating renal hemodynamics. Multispectral optoacoustic imaging showed that cecal ligation and puncture (CLP)-induced septic injury cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…In recent studies, we identified a significantly increased plasma level of EVs in patients and animals with trauma and sepsis, correlating with exacerbated proinflammatory response and cellular injury (Beard et al., 2016). We also observed greatly increased palmitoylation and DHHC21 activity under inflammatory conditions (Beard et al., 2016; Yang et al., 2021). DHHC21, unlike other DHHCs, is localized in plasma membrane, which allows it to dynamically regulate the function of many plasma membrane‐associated proteins involved in EV generation, such as G protein‐coupled receptors, G proteins, and phospholipases (Beard et al., 2016; Fan et al., 2020; Yang et al., 2021).…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…In recent studies, we identified a significantly increased plasma level of EVs in patients and animals with trauma and sepsis, correlating with exacerbated proinflammatory response and cellular injury (Beard et al., 2016). We also observed greatly increased palmitoylation and DHHC21 activity under inflammatory conditions (Beard et al., 2016; Yang et al., 2021). DHHC21, unlike other DHHCs, is localized in plasma membrane, which allows it to dynamically regulate the function of many plasma membrane‐associated proteins involved in EV generation, such as G protein‐coupled receptors, G proteins, and phospholipases (Beard et al., 2016; Fan et al., 2020; Yang et al., 2021).…”
Section: Introductionsupporting
confidence: 60%
“…Palmitoylated proteins on EVs were isolated using resin‐assisted capture as previously described (Beard et al., 2016; Mariscal et al., 2020; Yang et al., 2021). EV samples were lysed in lysis buffer (100 mM HEPES, 25 mM NaCl, 1 mM EDTA, 10 μM palmostatin B, Roche protease inhibitor tablet, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is indeed not clear whether β1-AR is palmitoylated on C358 only (Warne et al, 2009), or also on C392, C393, and C414 (Zuckerman et al, 2011) (Figure 2a). Two groups observed that DHHC21 is responsible for β1-AR palmitoylation (Marin et al, 2016;Yang et al, 2021). DHHC21 essentially localizes to the Golgi apparatus (Chopard et al, 2018;Fernández-Hernando et al, 2006;Tonn Eisinger et al, 2018).…”
Section: Palmitoylation Of β1-armentioning
confidence: 99%